Analisis Kualitas Pelayanan Publik Di Kelurahan Kamundu Kabupaten Merauke - Hubertus Oja (Sekolah Tinggi Ilmu Administrasi Karya Dharma, 2026)
The purpose of this study is to analyze the quality of public services in Kamundu Village, Merauke Regency. This study uses a qualitative research method with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The data analysis technique uses an interactive analysis method which includes data reduction, data presentation, and conclusion drawing. Based on the discussion above, which is an interpretation of the research results, the conclusion of this study is that the quality of public services in Kamundu Village is not yet effective when viewed from the indicators of responsiveness, responsibility, and accountability. In terms of responsiveness, there is still a low level of community adaptation in fulfilling requirements in the service process, which occurs due to a lack of effective socialization. In terms of responsibility, it was found that there is a lack of clarity regarding service time to provide certainty and clear information about when a service process will be completed or fulfilled. Meanwhile, in terms of accountability in service delivery, supervision in the public service process has not been optimal, which impacts accountability in the service activities provided.